(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Nowadays people spend more and more time in front of various screens and they barely take notice of any plants and animals living in their environment. This problem has grown so big that it has even got its own name: plant blindness. The term describes the phenomenon that people are not aware of the plants living in their close environment and do not have the desire to get to know them either. Bringing together educators and parents could provide a possible solution to this problem. Consequently, well-trained teachers play an important role, along with teacher training institutions. Our presentation contains a survey which examines the level of plant awareness and knowledge among fourth year teacher training students.